Pengaruh Institutional Ownership, Likuiditas, dan Firm Size terhadap Kebijakan Utang pada Perusahaan Sektor Pertambangan di BEI Tahun 2019-2022 - Diah Nuraini; Evi Yuniarti; Artie Arditha Rachman (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research was conducted to determine the effect of institutional ownership, liquidity and firm size on debt policy in mining sector companies listed on the Indonesia Stock Exchange (BEI) in 2019-2022. This research uses 3 independent variables in the form of institutional ownership which is measured by comparing shares owned by institutions to outstanding shares, liquidity which is measured by the current ratio, and firm size which is measured by ln.total assets. The dependent variable is debt policy, measured using the debt to equity ratio. The population in this research is 87 mining sector companies registered on the IDX in 2019-2022. Sampling used purposive sampling technique. The total research sample was 45 companies with 144 financial report data tested using multiple linear regression analysis. The results of the research that has been conducted show that partially and simultaneously institutional ownership, liquidity and firm size has an effect debt policy.